Pengaruh Praktik Manajemen Stratejik terhadap Kinerja Koperasi pada KPRI Propinsi Riau - Tanjung, Amries Rusli (Jurnal Aplikasi Manajemen, 2008)
The study aims to find out the effects of strategic management practices on KP-RI primary cooperative performance. The hypothesis proposed was that strategic management practices had positive and significant impacts on KP-RI primary cooperative performance, 110 KPRI units of 156 population in Riau Province were taken as samples. Survey was used as method whereas data were collected through questionairre posed to cooperative's management. The questionaire was arranged based on 5 scale of Likert's method. Statistic Descriptive Analysis, Confirmatory Factorial Analysis, and Path Analysis were used as analysis tools. To test the model and relations developed in previously Structural Equation Model (SEM) was used with the help of software AMOS 5.0. The results were then tested with regression weight / loading factor as well as t-test on regression weight/loading faktor/coefficient ë to test the hypothesis. The results showed that there was significant and positive effects of strategic management practices on primary cooperative's performance in Riau Province.